Counseling blood donors seropositive for human T-lymphotropic virus types I and II in a developing country Aconselhando o doador de sangue soropositivo para o Vírus Linfotrópico Humano tipo I/II em um país em desenvolvimento - Valéria M. A. Passos; Fátima F. Calazans; Anna Bárbara F. Carneiro-Proietti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Human T-lymphotropic virus types I and II (HTLV-I/II) are blood-transmitted retroviruses associated with leukemia, myelopathy, and uveitis. From 51,135 eligible blood donors at the Fundação Hemominas tested in 1993, 689 (1.35%) were repeatedly reactive to HTLV-I/II antibodies by enzyme immunoassay and were notified accordingly. Routes of transmission and preventive measures were emphasized in the orientation. Supplementary laboratory tests should be available and free of cost. Health services should recommend the use of latex condoms and make them available. Avoiding shared use of needles or syringes is important for both the seropositive donor and public health in general. In a country with such widespread malnutrition, the benefits of breast-feeding usually outweigh the risks of virus transmission. Based on our experience, we recommend that: 1) identical orientation be given to donors by all health professionals involved in counseling; 2) level of schooling be considered and information provided accordingly; 3) donors be assisted in understanding and assessing available information; 4) psychological assistance be provided to anxious or depressed donors; and 5) joint counseling be offered to donors with stable partners. Os vírus linfotrópico humano tipos I e II (HTLV-I/II) são retrovírus transmitidos por componentes celulares sanguíneos e associados à ocorrência de leucemia, mielopatia e uveíte. De 51.135 doadores de sangue da Fundação Hemominas testados em 1993, 689 (1,35%) foram repetidamente reativos a anticorpos contra HTLV-I/II no ensaio imunoenzimático e foram devidamente notificados. As vias de transmissão e medidas de controle foram enfatizadas na orientação. Testes laboratoriais suplementares devem ser disponíveis e gratuitos. O uso de preservativos deve ser recomendado e os mesmos serem disponíveis nos serviços de saúde. O doador soropositivo e os serviços de saúde não devem reutilizar agulhas e seringas. Sendo a desnutrição infantil um problema grave no país, o benefício da amamentação sobrepõe-se ao risco de transmissão de viroses. Baseados em nossa experiência, recomenda-se: 1) a mesma orientação deve ser dada por todos os trabalhadores de saúde envolvidos no aconselhamento do doador, 2) o nível educacional deve ser considerado e as informações fornecidas de acordo com as necessidades individuais; 3) deve-se auxiliar o doador a compreender e criticar as informações disponíveis e 4) fornecer assistência psicológica adequada a doadores ansiosos ou deprimidos e 5) se o doador tem um paceiro estável, as informações devem ser dadas ao casal, simultaneamente.